A study of the circulation of West Nile virus, Sindbis virus, Batai virus and Usutu virus in mosquitoes in a potential high-risk area for arbovirus circulation in the Netherlands, "De Oostvaardersplassen". Issue 29 (2011) - Reusken, Chantal; Vries, Ankje De; Ceelen, Erik; Beeuwkes, Jacob; Scholte, Ernst-Jan
No abstract available